Español - Español, Español; Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
A taxonomic revision about the zahareñas ( Sideritis L.) from West Andalu cia has been realized, being they represent for 10 taxons. They, except Sideritis montana L. subsp. ebracteata (Asso) Murb., are very use in popular therapeutic. To facilitate their identification, key, diagnostic characters and iconography are included, indicating moreover their general distribution and in West Andalucia, this last showed in a map, ecological and fenological characteristics, and popular utilization.